SweDiagnostics - Språkbanken Text (University of Gothenburg, 2024)
Swedish version (Super)GLUE Diagnostic

Svenska versionen av (Super)GLUE diagnostik
SweDiagnostics
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik